Methylformate formation from methanol and CO ON Cu/ZnO catalysts - CHUNG, MJ; PARK, KY; LEE, BG; IHM, SK (KOREAN INST CHEM ENGINEERS, 1993)
The reaction mechanism for the methylformate formation on Cu/ZnO catalysts from methanol and CO was investigated by the labeling study with C-13 methanol. It was found that methylformate could be formed through two parallel reaction routes, i.e., methanol-formaldehyde reaction and carbonylation of methanol depending upon the catalyst composition as well as the reaction conditions. The major reaction route on the high ZnO-content catalyst (Cu/ZnO=30/70) was found to be the methanol-formaldehyde reaction, and changed to the carbonylation reaction with the increase of CO partial pressure. On the other hand, the major reaction route on the high Cu-content catalyst (Cu/ZnO=80/20) remained as methanol-formaldehyde reaction even under the high CO pressure.